Generation Z in Search of Leadership - Model of Intergenerational Leadership for Creating Commitment (MILCC) - Tidhar LEV (Cross-Cultural Management Journal)
Generation Z is integrating into the fast-changing work world. The effects of its entry are rapid employee turnover, perceptions of no commitment to organizations, and difficulty in understanding employee needs. This article presents a model for creating commitment for Generation Z employees based on research on executive leadership's impact on Generation Z employee commitment. The research used a mixed methods research methodology based on a qualitative study consisting of interviews with managers in Israeli high-tech and a quantitative study of 180 Generation Z employees working in Israeli high-tech. The Model of Intergenerational Leadership for Creating Commitment (MILCC) is based on research findings showing that managers' leadership was the most significant factor in employee engagement. The model presents four circles of influence producing employee engagement and five core management and leadership components managers must strengthen to create commitment: authentic leadership, agile management, soft skills, ability to build motivation, and digital leadership. This article and model reinforce the view that organizations and managers must change their approach to employees and organizational expectations alongside the changes in the world of work.